Behavioral Manipulation In Big Data Implementation: Systematic Literature Review - Hendi Sama; Mangapul Siahaan; Nancy Vanessa (LPPM Universitas Dian Nuswantoro, 2026)
This study investigated the phenomenon of behavioral manipulation in big data implementation through a systematic literature review of thirty peer-reviewed articles published between 2020 and 2025. The objective of the review was to provide a comprehensive understanding of the mechanisms, impacts, and mitigation strategies related to the use of big data for influencing human behavior. The review was conducted following the PRISMA 2020 framework, ensuring transparency and reproducibility in the selection and evaluation process. Out of an initial 250 records identified across major academic databases, 30 studies were ultimately included based on predefined inclusion and exclusion criteria. The analysis revealed that behavioral manipulation was primarily executed through algorithmic recommendation systems, dynamic pricing models, deceptive interface design, and data-driven persuasion techniques. The reviewed studies indicated that such practices compromised individual autonomy, shaped consumer and political decisions, and contributed to psychological strain and social inequality. The findings also highlighted the paradox of algorithmic transparency, showing that disclosure without user comprehension could legitimize manipulation rather than reduce it. Furthermore, evidence suggested that emerging interventions, such as dynamic consent mechanisms and independent algorithmic audits, showed potential in restoring trust and protecting user rights, although their implementation remained limited. Approximately 83.3% of the reviewed studies concluded that behavioral manipulation through big data is a multidimensional challenge requiring an integrated response that combines technical safeguards, ethical design, adaptive regulation, and enhanced digital literacy. Keywords - Behavioral manipulation, Big data implementation, Decision making